The family Apocynaceae (Apocynoideae and Rauvolfioideae) in the State of Morelos, Mexico - González-Rocha, Edith; Cerros-Tlatilpa, Rosa (Instituto de Ecología, A.C., 2015)
Results are presented for the study of Apocynaceae (Apocynoideae and Rauvolfioideae) in the state of Morelos, Mexico. We found ten genera and 14 species: Cascabela (2), Haplophyton (1), Laubertia (1), Mandevilla (3), Plumeria (1), Prestonia (1), Rauvolfia (1), Tabernaemontana(2), Thenardia (1) and Tonduzia (1). Subfamily Rauvolfioideae is well represented with six genera and eight species, whereas Apocynoideae has four and six, respectively. Most taxa grow in tropical deciduous forest, oak forest, gallery forest and coniferous forest. Six of the 29 endemic species of Mexico are present in Morelos: Cascabela thevetioides, Laubertia contorta, Mandevilla foliosa, M. holosericea,Tabernaemontana tomentosa y Thenardia floribunda. This study includes identification keys, descriptions, common names, specimen examined and recollected, elevation recorded, distribution maps and photographs.